AMPK deficiency in cardiac muscle results in dilated cardiomyopathy in the absence of changes in energy metabolism. (28th May 2015) - Sung, Miranda M.; Zordoky, Beshay N.; Bujak, Adam L.; Lally, James S.V.; Fung, David; Young, Martin E.; Horman, Sandrine; Miller, Edward J.; Light, Peter E.; Kemp, Bruce E.; Steinberg, Gregory R.; Dyck, Jason R.B.
Abstract: Aims: AMP-activated protein kinase (AMPK) is thought to be a central player in regulating myocardial metabolism and its activation has been shown to inhibit cardiac hypertrophy. Recently, mice with muscle-specific deletion of AMPK β1/β2 subunits (AMPKβ1β2-deficient mice, β1β2M-KO) have been generated and possess <10% of normal AMPK activity in muscle. However, how/if dramatic AMPK deficiency alters cardiac metabolism, function, or morphology has not been investigated. Therefore, the aim of this study was to determine whether a significant loss of AMPK activity alters cardiac function, metabolism, and hypertrophy, and whether this may play a role in the pathogenesis of heart failure. Methods and results: β1β2M-KO mice exhibit an approximate 25% reduction in systolic and diastolic function compared with wild-type (WT) littermates. Despite the well-documented role of AMPK in controlling myocardial energy metabolism, there was no difference in basal glucose and fatty acid oxidation rates between β1β2M-KO and WT mice. However, there was reduced AMPK-mediated phosphorylation of troponin I in β1β2M-KO and reduced ventricular cell shortening in the presence of low Ca 2+, which may explain the impaired cardiac function in these mice. Interestingly, β1β2M-KO mice did not display any signs of compensatory cardiac hypertrophy, which could be attributed to impaired activation of p38 MAPK. Conclusions: β1β2M-KO mice display evidence of dilated cardiomyopathy. This is the first mouse model of AMPK deficiency that demonstrates cardiac dysfunction in the absence of pathological stress and provides insights into the role of AMPK in regulating myocardial function, metabolism, hypertrophy, and the progression to heart failure.